SARS-CoV-2 evolution: emergence of the ‘Californian’ and ‘Indian’ variants - Vail, Eric (Henry Stewart Talks, 2021)
Status and efficiency of SARS-CoV-2 genetic surveillance in the USA, The identification of a ‘Californian’ variant, Epsilon, following a surge in Covid-19 cases in California in early 2021, The genetic characteristics of the Epsilon variant and the phenotypic advantages they provide, The more recent identification of a separate variant from India, the Delta variant: key characteristics and their implications